Orbital Compression Syndrome in a Child with Sickle Cell Anaemia: A Case Report And Review of Literature - Panda, Prateek Kumar (Journal of Nepal Paediatric Society, 2018)
Vaso-occlusive crises in sickle cell disease commonly involve bone marrow of the long bones and vertebrae. Involvement of bones with less marrow space, including the bones of the orbit, is reported rarely in the literature. The present case is a six year old boy, a known case of sickle cell disease, who presented with acute onset right upper and lower eyelid swelling, restriction of extraocular movement and pain. USG orbit showed a retro-orbital haemorrhage compressing on the orbit, probably due to orbital bone infarction. The child was managed successfully with red blood cell transfusion and intravenous antibiotics, without steroids and surgical intervention. This report highlights the importance of maintaining a high index of suspicion in patients with known sickle cell disease presenting with pain, orbital swelling and restriction of ocular movement. Timely red blood cell transfusion only may be sufficient for uneventful recovery, without steroids or surgical intervention. Expedient diagnosis of orbital compression syndrome in children with sickle cell disease is crucial because this is a potentially sight-threatening entity.